Determination of iodide and idoxuridine at a glutaraldehyde-cross-linked poly-L-lysine modified glassy carbon electrode - Pereira, F. C.; Fogg, A. G.; Ugo, P.; Bergamo, E. P.; Stradiotto, Nelson Ramos [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Wiley-Blackwell, 2005)
The detection limit (about 0.017 mu g mL(-1)) for voltammetric determination of iodide (peak at +0.87 V vs. Ag/AgCl at pH 2) at a glutaraldehyde-cross-linked poly-L-lysine modified glassy carbon electrode involving oxidation to iodine was found to be several orders of magnitude lower than that for the voltammetric determination on a bare glassy carbon electrode. This method was applied successfully to the determination of iodide in two medicinal formulations. Idoxuridine was determined indirectly at the same electrode by accumulating it first at -0.8 V vs. Ag/AgCl. At this potential the C-I bond in the adsorbed idoxuridine is reduced giving iodide, which is then determined at the modified electrode. The method was successfully applied to the determination of idoxuridine in a urine sample.
Keywords: glutaraldehyde-cross-linked poly-L-lysine modified glassy carbon electrode; iodide determination; idoxuridine determination; modified electrode